Pengembangan Mesin Pengiris Pisang Inovatif pada Usaha Olahan Pisang Cesy Lia - Lina Maulidiana; Defrizal Defrizal; Martinus Martinus; Arnofdwi Ferdiza; Hikmal Yusuf (Jurnal Solusi Masyarakat (JSM), 2026)
Community Service activities for Cesy Lia banana chip MSMEs are carried out through the Development of an Innovative Banana Slicing Machine. Cesy banana chip MSMEs have high economic potential due to abundant raw materials, relatively simple production technology, and stable market demand. However, the "Celsy Lia" Household Industry faces problems in the production aspect, especially in the process of slicing raw bananas which is still done manually using a simple machine that is less efficient. This condition has an impact on low production capacity, inconsistency of slice thickness, high labor costs, and decreased product quality. Partner problems in the management aspect, there are no operational standards for better business sustainability and financial management that is not well organized so that partners cannot clearly know the shortcomings and advantages of the business, so that they can create strategies to increase revenue. The service team provides solutions in the form of Appropriate Technology Tools in the form of innovative banana slice machines in order to increase revenue and provide an understanding of structured management management for business sustainability.